The Relationship Between Activities Using Learning Media to Read Fluently and Speaking Ability in Early Age Children - Siti Nabilah (Tajdid Al-Athfal, 2024)
The aim of this research is to determine the reality of media usage activities for reading fluency in Group B RA Persis 180 Miftahul Jannah Andir Bandung City, the reality of early childhood speaking abilities in Group B RA Persis 180 Miftahul Jannah Andir Bandung City, and the relationship between media use activities learning to read fluently with speaking skills for early childhood in Group B RA Persis 180 Miftahul Jannah Andir Bandung City. This research uses quantitative correlational methods. The subjects in this study were 15 children in Group B RA Exactly 180 Miftahul Jannah Andir Bandung City. Data collection techniques were carried out using observation sheets. The research results were processed using partial analysis of items per indicator, normality test, linear regression test, correlation and determination coefficients, hypothesis testing. The results of the research show that the activity of using learning media for reading fluency with results (83.24) and the speaking ability of young children with results (83.65) are in the very good category. The relationship between the activity of using learning media for reading fluency and the speaking ability of young children in Group B RA Persis 180 Miftahul Jannah Andir Bandung City can be seen from the results of the correlation coefficient which produces a value of 0.59 indicating a fairly strong/medium level of relationship.